From eviction to evicting: Rethinking the technologies, lives and power sustaining displacement. (August 2021) - Baker, Alexander
An unnamed shift has occurred in geographies of eviction. While past research focused on the causes and effects of eviction in political economy, state power, and cultural difference, emerging work emphasises the subjective experience and sustaining practices of eviction as it happens. This paper makes the case for this turn away from causes and outcomes of 'eviction', and towards 'evicting' as a set of material technologies and practices that sustain displacement, and explores the implications of such a shift. Research into lived durations of eviction, evicting technologies, and eviction enforcement agencies opens up new conceptual and political fields of intervention.